Hierarchia wschodnich biskupów w historiografii kościelnej V wieku - Bralewski, Sławomir (Vox Patrum, 2012)
Francis Dvornik has expressed the view that, in the Eastern part of the Empire, the principle of accommodation dominated over the principle of the apostolic origin. The situation, he maintained, resulted from the fact that the aforementioned area included excessively numerous sees which were either established by one of the Apostles or were considered to be somehow connected with their activities. Does the conclusion of the Czech researcher find any justification in the way the precedence of bishoprics is depicted in the Greek ecclesiastical historiography of the fifth century? The present article is to give an answer to the question. The analysis of the ecclesiastical historiography in question demonstrates that Eusebius of Caesarea, who wrote in the IV th century, while setting a hierarchy of bishops was guided first and foremost by the principle of accommodation. The church historians, however, who compiled their works a mere century later put a decisively lesser stress on Eusebius’ predilection in that matter. Although the narrative of Philostorgius, since fragmentary, is hard to interpret, Socrates’ attitude displays a marked tendency of favoring the importance of the apostolic origin, which was most probably taken over from Rufinus of Aquileia. Sozomen tended to tell the difference between the official hierarchy of bishops, which was based on the principle of accommodation, and the structure of bishoprics connected with the Apostles. Theodoretus, in turn, tended to connect both the principles, however, preferring the idea of the Church originated by saint Peter, accordingly of the ecclesiastic structure based on the principle of the apostolic origin. As a consequence, and contrary to F. Dvornik’s thesis, it should be concluded that (at least) the authors of the Ecclesiastic Histories of the fifth century were in favor of the principle of the apostolic origin and maintained it was over the principle of accommodation.